The European Model of Progressive Salary Taxation: Array - Sargu, Nicu (Acta Universitatis Danubius. Œconomica, 2022)
This article presents an applied theoretical research on the application of the progressive taxation system used in a member country of the European Union such as Germany on the budget revenues of the Republic of Moldova. The aim of the research was to estimate the impact of budget revenues by modeling the progressive taxation system. Achieving the goal was summarized by the objectives set by researchers on the synthesis and analysis of theoretical approaches to income in the form of wages and the identification of elements of taxable income. At the same time, the information and statistics on the forms of budget receipts in the form of income tax of individuals from the Republic of Moldova and a member country of the European Union such as Germany were presented and analyzed.